INVESTMENT AND INNOVATION FACTORS IN THE MECHANICAL ENGINEERING OF THE REGIONS IN THE IMPLEMENTATION OF THE PROGRAMME OF DEVELOPMENT OF THE ARCTIC ZONE OF THE RUSSIAN FEDERATION - V. N. Borisov; O P. Pochukaeva (Модернизация, инновация, развитие, 2018)
Purpose: in the article we have carried out research of efficiency of investment and innovative-technological activity in the mechanical engineering of the regions involved in the Program development of the Arctic zone of the Russian Federation. Presented the approach to the assessment of efficiency of investment and technological innovation activities in these regions and influence the development of mechanical engineering.Purpose: in the article we have carried out research of efficiency of investment and innovative-technological activity in the mechanical engineering of the regions involved in the Program development of the Arctic zone of the Russian Federation. Presented the approach to the assessment of efficiency of investment and technological innovation activities in these regions and influence the development of mechanical engineering.Methods: suggested and used the tools of forecasting and analytical studies of the effects that result from the impact of the investment and innovative-technological factors on the development of industry in the regions, with priority mechanical engineering.Results: as a result, we have got a quantitative evaluation of investment and innovative factors for the development of regional economies. We also have built integrated indicators of economic and technological effects arising from the investment and innovative-technological activity involving machinery production in these regions.Conclusions and relevance: interpretation of the results shows that in most regions innovation and investment activities have a significant impact on the competitiveness of manufactured machinery products and on the export potential of the region. The potential of regional economic development lies in the interaction of domestic production and the innovative technological component. In the course of the implementation of the Arctic project, the demand for new technologies and scientific results is formed, the specific consumption of natural resources is reduced through the use of resource-saving technologies, investment activity is activated, ensuring the growth of production fixed assets and improving the balance of payments in foreign trade in industrial products.